Genre and Discourse (and Zombies), an Introduction in Pictures. Issue 1 (11th August 2015) - Labarre, Nicolas
Abstract : This five-page comic, contextualised with a research note, provides an introduction to discursive approaches to genre, inspired by Rick Altman's Film/Genre (1999 ). It seeks to demonstrate the necessity to go beyond textual or prescriptive approaches, using the example of zombie films. The comic is arguing that some films that contain zombies are not usually seen as being part of the zombie film genre. The work proposes that our perception of genre in those cases relies on various discourses that frame our reading of the texts themselves. This framing operation is at once the function and the nature of genre.